Elements of symbolism in Dr Salim Akhtar's Short Stories - Faiza Urooj; Dr. Muahmmad Afzal Butt (Zaban-o-Adab, 2021)
Short stories (Fiction) as compared to other kinds of leterature, presents diverse angles of life in a more realistic way. In Urdu fiction, the tradition of symbolism is in vogue for centuries. After the establishment of Pakistan, in a very short time, political, societal, economical and psychological behaviours, in the mode of symbol, found place in the art of Intezar Hussain, Ahmad Javed, Rasheed Amjad, Anwar Sajjad, Sarindar Perkash and then in the work of creative writers like Dr. Sleem Akhter. He symbolised "Basti", "Kath Putli", "Shajar", "Sehraa", "Pahar", "Kushbu", "Badbu" and various animals and birds in which owl, vulture, dog, donkey and scorpion are remarkable. He has clear tendency towards mythology, societal and political symbolism. He has proved his artistic insight in selecting events details to stable symbol in his fiction. The symbolic fiction of Dr. Sleem Akhtar is unique wealth in Urdu literature. In the history of fiction, his name is so remarkable.